2009
DOI: 10.1042/bj20082222
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of intestinal mucin MUC2 expression by short-chain fatty acids: implications for epithelial protection

Abstract: SCFAs (short-chain fatty acids), fermentation products of bacteria, influence epithelial-specific gene expression. We hypothesize that SCFAs affect goblet-cell-specific mucin MUC2 expression and thereby alter epithelial protection. In the present study, our aim was to investigate the mechanisms that regulate butyrate-mediated effects on MUC2 synthesis. Human goblet cell-like LS174T cells were treated with SCFAs, after which MUC2 mRNA levels and stability, and MUC2 protein expression were analysed. SCFA-respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
297
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 490 publications
(340 citation statements)
references
References 44 publications
9
297
1
3
Order By: Relevance
“…Treatment with butyrate, an HDAC inhibitor, induces differentiation as noted by the increased expression of intestinal alkaline phosphatase (IAP), an enterocyte differentiation marker, and Mucin2 (MUC2), a goblet cell differentiation marker in LS174T cells. 26,27 We have shown that βHB inhibits HDAC in Caco-2 cells. To determine whether βHB also increases goblet cell differentiation, we treated LS174T cells with βHB.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment with butyrate, an HDAC inhibitor, induces differentiation as noted by the increased expression of intestinal alkaline phosphatase (IAP), an enterocyte differentiation marker, and Mucin2 (MUC2), a goblet cell differentiation marker in LS174T cells. 26,27 We have shown that βHB inhibits HDAC in Caco-2 cells. To determine whether βHB also increases goblet cell differentiation, we treated LS174T cells with βHB.…”
Section: Resultsmentioning
confidence: 99%
“…Lactic acid producers such as Lactobacillus, Lactococcus, Bifidobacterium and Streptococcus were higher in the faeces of children pre-diagnosed with autoimmune diabetes (Brown et al, 2011). The fate of lactate is crucial in determining intestinal health as conversion to butyrate results in mucin synthesis (Barcelo et al, 2000;Burger-van Paassen et al, 2009;Finnie et al, 1995;Shimotoyodome et al, 2000) and tighter junctions (Peng et al, 2007(Peng et al, , 2009, while conversion to other SCFA, such as propionate and acetate does not induce mucin synthesis (Brown et al, 2011). Mucin is a glycoprotein made by the host that maintains the integrity of intestinal epithelium (Brown et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In healthy mammas, there is a dynamic balance between mucin release by goblet cells and mucin loss through physical and proteolytic processes (Mart ınez-Maqueda et al, 2013a, b). In addition to internal factors such as hormones and cytokines, dietary regulation of mucin secretion has also been mentioned (Morel et al, 2003;Burger-van et al, 2009;Moughan et al, 2013).…”
Section: Prebiotic Effectsmentioning
confidence: 99%